Upaya Pendidikan Multibudaya Menumbuhkan Karakter Bangsa - Ahyani, Nur; Lestari, Neta Dian (PPSDP Undergraduate Journal of Educational Sciences, 2025)
This study aims to explore the implementation of multicultural education in Indonesia and its impact on the formation of national character. Literature study was conducted to identify challenges, opportunities, and solutions in developing effective multicultural education. The results of the study indicate that multicultural education has great potential in fostering an attitude of tolerance, respecting diversity, and strengthening national unity. However, its implementation still faces various obstacles, such as lack of resources, limited understanding, and lack of policy support. This study concludes that multicultural education is a long-term investment to build an inclusive and harmonious society. Some recommendations proposed include strengthening policies, curriculum development, teacher training, and involving the community in efforts to realize multicultural education.